Testing the Electronic Personal Health Record Acceptance Model by Nurses for Managing Their Own Health - Gartrell, K.; Trinkoff, A.M.; Storr, C.L.; Wilson, M.L.; Gurses, A.P. (Applied Clinical Informatics, 2015)
Background: To our knowledge, no evidence is available on health care professionals’ use of electronic personal health records (ePHRs) for their health management. We therefore focused on nurses’ personal use of ePHRs using a modified technology acceptance model.Objectives: To examine (1) the psychometric properties of the ePHR acceptance model, (2) the associations of perceived usefulness, ease of use, data privacy and security protection, and perception of self as health-promoting role models to nurses’ own ePHR use, and (3) the moderating influences of age, chronic illness and medication use, and providers’ use of electronic health record (EHRs) on the associations between the ePHR acceptance constructs and ePHR use.Methods: A convenience sample of registered nurses, those working in one of 12 hospitals in the Maryland and Washington, DC areas and members of the nursing informatics community (AMIA and HIMSS), were invited to respond to an anonymous online survey; 847 responded. Multiple logistic regression identified associations between the model constructs and ePHR use, and the moderating effect.Results: Overall, ePHRs were used by 47%. Sufficient reliability for all scales was found. Three constructs were significantly related to nurses’ own ePHR use after adjusting for covariates: usefulness, data privacy and security protection, and health-promoting role model. Nurses with providers that used EHRs who perceived a higher level of data privacy and security protection had greater odds of ePHR use than those whose providers did not use EHRs. Older nurses with a higher self-perception as health-promoting role models had greater odds of ePHR use than younger nurses.Conclusions: Nurses who use ePHRs for their personal health might promote adoption by the general public by serving as health-promoting role models. They can contribute to improvements in patient education and ePHR design, and serve as crucial resources when working with their individual patients.Citation: Gartrell K, Trinkoff AM, Storr CL, Wilson ML, Gurses AP. Testing the electronic personal health record acceptance model by nurses for managing their own health: A cross-sectional survey. Appl Clin Inf 2015; 6: 224–247http://dx.doi.org/10.4338/ACI-2014-11-RA-0107
Keywords: Personal health record; nurse; data privacy and security; health promotion; technology acceptance model